Practice in industry training in fish culture - Juliano, Rogelio O. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1952)
The banos or mfilkfish, chanos chanos can be considered the national fish of the Philippines. The production of this popular fish did not meet the demand of the population of the nation. At present our population is about twenty million. Because the areas developed for the culture of bangos is still small and the cost of production is quite high the supply barely meets the people's demand. Hence, this study on the transplantation of bangos from saline water to fresh water was undertaken, to see the feasibility of stocking our fresh water ponds and lakes with milkfish and thus increasing the production with less expense. They say in India that the milkfish could thrive in fresh water and even grow faster there than they are in saline waters. If this is true there, will it be also hold true here in the P. I. so the study of the bureau of the Fisheries, in the town of Malabon, province of Rizal. This station is equipped with the knowledge of how those experiments were performed in India. Mr. Rafael Prado and I made the trials under the advisorship of Mr. Herminio Rabanal. He worked this more than 5 months. Besides those experiments in dagat-dagatan my work included some field trips to San Juan Reservoir. The latter part of my practice in industry training was devoted to the bibliography of chanos chanos. This was mostly library work, digging up all literature from the early scientific papers to the present time.
Keywords: Fish-culture.